Allergy to Technetium-Labelled Nanocolloidal Albumin for Sentinel Node Identification - Chicken, Dennis W (The Royal College of Surgeons of England, 2007)
Optimal sentinel node identification requires using the combination technique with blue dye and radiocolloid. Allergic reactions to the common blue dyes in use are well recognised. In this report, we present a patient with breast carcinoma who developed a type I hypersensitivity reaction to intradermal injection of technetium-99m labelled nanocolloidal albumin. While reactions to colloids are rare, and in this case minor, operators using this radiopharmaceutical should be prepared for a potential severe anaphylactic reaction.